FACTORS ASSOCIATED WITH KNOWLEDGE AND PRACTICES IN BREASTFEEDING AND COMPLEMENTARY FEEDING - Valencia Coloma, Jeny Patricia (2024)
Introduction: This study aims to identify factors associated with knowledge and practices in Breastfeeding and Complementary Feeding. Objective: The objective was to assess 66 breastfeeding women in Quito, Ecuador, to determine these factors. Methods: Sociodemographic and knowledge/practice questionnaires were utilized. Analysis was conducted using SPSS v25, Kruskall-Wallis, and Cronbach's alpha. Results: Cronbach's alpha of 0.71; significant correlations (p<0.05) in age, marital status, number of births, place of residence, etc. Lack of knowledge of breastfeeding practices is associated with the early introduction of complementary foods. Conclusions: Poor suction technique contributes to insufficient milk production and painful breastfeeding, influencing the introduction of complementary feeding before 6 months. In summary, various elements are associated with knowledge and practices in breastfeeding and complementary feeding.